The Effect of Media Composition and Soaking Period of Auxin on Bud Chip Technique Sugarcane Seedling - Erliandi Erliandi; Ratna Rosanty Lahay; Toga Simanungkalit (Jurnal Agroekoteknologi, 2015)
The objective of the research was obtained the appropriate of media composition and soakingperiod of auxin toward growth of bud chip technique sugarcane seedling. The research wasconducted at experimental field of Tanjung Jatti Estate Binjai PTPN II (± 50 m asl.) in April – Juny2014 using a randomized block design with two factors. The first factor was media compositionwith levels: 50:50, 70:30, and 30:70 (% top soil: % blotong compost), and the second factor wassoaking period of auxin with levels: 10, 20, and 30 minutes to consentration 2 ml/L with threereplications. The result of this research showed that application of media composition wassignificant effected on seedling growth percentage at 1 week after planting (WAP), plant height andstem diameter at 6 WAP, leaf total at 4 and 6 WAP, leaf area at 8 WAP, sturdiness value, shoot/rootratio and seedling quality index. The soaking period of auxin was significant effected on leaf area at 8 WAP and shoot/root ratio. Interaction of both was significant effected only on leaf total at 2 WAPwith M1T3 was the highest. Keywords: bud chip, media, auxin, sugarcane